Spatial Control, Precarity, and Union Resistance in Digital Remote Work: An Analysis of ‘Work From Home’ in US and Canadian Call Centres - Doellgast, Virginia; O’Brady, Sean; Kim, Jeonghun (Work, Employment and Society, 2026)
This article analyses the experiences of US and Canadian call centre workers and their unions with the shift from physical call centres to ‘work from home’ (WFH) arrangements. Drawing on interviews, focus groups and a worker survey, the authors find that the shift enabled new forms of spatial control grounded in worker preferences for remote work and associated with different forms of precarity. Management control over the physical location of work could increase job insecurity; control over the costs and risk associated with WFH arrangements could increase income insecurity; and control over communication between workers and with their unions could increase collective representation and voice insecurity. Local unions engaged in modes of resistance to spatial control, but with uneven success. Findings suggest that labour power requires union strategies that both defend WFH rights and develop protections targeted at forms of precarity associated with being able to work from home.

Control and Insecurity in Australian and Canadian Universities during the COVID-19 Pandemic - Peetz, David; O’Brady, Sean; Weststar, Johanna; Coles, Amanda; Baird, Marian; Cooper, Rae; Charlesworth, Sara; Pyman, Amanda; Ressia, Susan; Strachan, Glenda; Troup, Carolyn (Relations industrielles / Industrial Relations, 2022)
We studied 14 universities across Canada and Australia to examine how the COVID-19 crisis, mediated through management strategies and conflict over financial control in higher education, influenced workers’ job security and affective outcomes like stress and happiness. The countries differed in their institutional frameworks, their union density, their embeddedness in neoliberalism and their negotiation patterns. Management strategies also differed between universities. Employee outcomes were influenced by differences in union involvement. Labour cost reductions negotiated with unions could improve financial outcomes, but, even in a crisis, management might not be willing to forego absolute control over finance, and it was not the depth of the crisis that shaped management decisions.
Keywords: Analyse comparative; Australia; Australie; COVID-19; Canada; Contrôle; Covid-19; Stratégies de gestion; Syndicat; Travailleurs universitaires; comparative analysis; control; contrôle financier; financial control; management strategies; negotiation pattern; négociation collective; union; university workers